FRI0384 Background Treatment and Disease Variables Affecting High Placebo Responses in Systemic Lupus Erythematosus (SLE) Trials: Update from the Soccit Program. (10th June 2014) - Kalunian, K.C.; Kim, M.Y.; Baskaran, A.; Daly, R.P.; Merrill, J.T.
Abstract : Background: Most clinical trials for SLE allow various background immune suppressants to which investigational agents are added (1). The impact of these standard-of-care (SOC) treatments or clinical variables on placebo group response rates remains uncertain (2). Objectives: To compare effects of background treatments and disease variables on outcome in SLE trials of patients on mycophenolate mofetil (MMF), azathioprine (AZA) methotrexate (MTX) and high dose cyclophosphamide (IVCY). Methods: Data were merged from 933 SLE patients randomized to placebo plus SOC in 3 nephritis and 3 non-nephritis trials. Response and flare rates were based on available data using the BILAG Index (3). Results: In nephritis trials baseline occurrence of ≥ BILAG A was almost universal (94% MMF, 96% IVCY). In other trials 64% of MMF patients had ≥1 A vs only 53% AZA, 52% MTX, 58% other (p=0.06). Total baseline BILAG scores were MMF: 26.2 vs others: 22.1 p=0.01. Early in trials steroid doses were higher in MMF patients (wk 12: MMF 27.6 mg vs AZA 24.3, MTX 23.6) but decreased by wk 52 (MMF 12.6, AZA 13.3, MTX 7.2). BILAG response (1 grade improvement in baseline A or B scores without ≥1 new A or 2 new B) rates did not differ in nephritis trials at 24 wks (MMF 33% vs IVCY 31%, adjusted for steroids, p=0.63). In non-nephritis trials improvement at wk 52 was MMF 41%, AZA 35% MTX 28% (p=0.07 adjusted for steroids). Mucocutaneous (MC)-specific BILAG improvement was AZA 54% vs MMF 46%, MTX 47%. Musculoskeletal (MS) improvement was MMF 59%, AZA 54%, MTX 28%. Flare rates (rate/pt yrs) were lower in MMF vs IVCY patients in nephritis trials: all flares: (≥2 new B) 1.22 vs 1.34 (p=0.23), severe flares: (≥1 A) 1.02 vs 1.23 (p=0.03). In non-nephritis, flare rates were highest in MMF and lowest with AZA (all flares: AZA 1.24 vs MMF 1.87 (p=0.04) and MTX 1.42 (p=0.53), severe rates: AZA 0.66, MMF 1.29 (p=0.01), MTX 1.20 (p=0.02). Only 11.6% of MMF patients had both flare and improvement. Patients with ≥1A at baseline had more flares compared to moderate patients: rate/pt yr=2.39 vs 1.03 for MMF (p=0.01), 1.40 vs 0.91 for all others (p=0.02), severe flare rates: 1.87 vs 0.34 MMF (p=0.0013), 1.15 vs 0.43 others (p=0.0001). Severe flare rates in the MC system: AZA 0.16 vs MMF 0.45 (p=0.09) and MTX 0.5 (p=0.07) and MS: AZA 0.23 vs MMF 0.54 (p=0.08) and MTX 0.87 (p=0.004). Conclusions: In nephritis trials, placebo patients treated with MMF had equal response and fewer flares than IVCY. In non-nephritis trials, MMF patients had high response driven by MS system, but also high flare rates. Those who flared were more active at baseline and unlikely to improve at week 52, potentially defining two MMF outcome subpopulations. AZA-treated patients in non-nephritis trials had high response rates (not organ-specific) and lowest flare rates. Assuming the likelihood of treatment selection bias, these data do not illuminate treatment efficacy, but provide insight for trial designs by distinguishing factors, definable at entry, predictive of high placebo group responses. References: Bruce IN et al., Rheumatol (Oxford). 2010;49:1025. Steinman L et al., Nature Med 2012;18:59. Kalunian KC et al., Arthritis Rheum 2013:S. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5895